FRI0492-HPR Life stories, gender and chronic autoimmune diseases: results of a qualitative study. (23rd January 2014) - Stamm, T.; Duer, M.; Sadlonova, M.; Stoffer, M.; Haider, S.; Smolen, J.
Abstract : Background: Functioning in daily activities is commonly regarded as one of the most important outcomes in people with chronic rheumatic diseases, although there is a lack of data comparing the experiences of patients with different chronic autoimmune diseases and scarce data comparing between women and men. Objectives: The aim of this qualitative study was to describe functioning from the perspective of people with different chronic autoimmune diseases, to compare between diseases and with so-called healthy people without a chronic autoimmune disease and to compare between women and men. Methods: Seventy-five people with a chronic autoimmune disease and 15 healthy people were interviewed twice using a biographic narrative interview style. Fifteen people had rheumatoid arthritis (RA), 15 Scleroderma (SSc), 15 Systemic Lupus Erythematosus (SLE), 15 Crohn's disease (CD), 15 Diabetes Type 1 (D). All interviews were transcribed and analysed by using a narrative biographic method. To ensure rigor and accuracy of the analysis, reflective research diaries were kept by the researchers and a large part of the data analysis was performed by two to three people together. Results: Regardless if people had a disease or not, functioning in daily life was experienced positively when a balance between challenging and rewarding activities, as well as a balance between physical activities and rest was represented. The popular concept "work-life balance" was only meaningful for 7 (9%) of the participants. People with chronic autoimmune diseases faced several problems which were hardly covered in their clinical assessments, such as difficulties when caring for others, decreased career perspectives or problems of over-compensation. For example, participant "SSc 8" (female, age 69, retired) described her current main problem in taking care of others: "I have to take care for my grandchildren, they cannot stay the whole day in kindergarten and I have to pick them up, I have to drive 45 minutes home, it is very difficult, but I promised that I will do it, because I love my children." Participant SLE 9 (female, age 50, full-time paid work) felt that she could not be as ambitious as her colleagues in her professional career: "I was sitting at the computer until 12-13 hours per day, so the index finger was damaged. Because we never had children, I could work in principle the whole day, but I felt exploited, they others have their career, but I do not know if I could do it ... I wanted to over-compensate, to show that I could do it – despite my disease." Conclusions: Functioning in daily activities may differ largely between women (more involved in caring for others, more inconsistent professional careers) and men (prioritise work commitments over health concerns) in chronic autoimmune diseases. Several problems of patients with chronic autoimmune diseases are not covered by the instruments most commonly used to assess functioning in daily life. These instruments may not be sensitive enough to detect changes of non-pharmacological interventions of health professionals. Instruments that allow patients to select target activities may be an alternative. Disclosure of Interest: None Declared